Implications of instructional strategies in sport teaching: a nonlinear pedagogy-based approach - Alexander Gil; Duarte Araujo; Luis García-González; Maria Perla Moreno; Fernando del Villar (Asociación Española de Ciencias del Deporte, 2014)
In this article, we have tried to establish the practical implications of instructional strategies in sport teaching.  Firstly, we have highlighted the importance of the Teaching Game for Understanding as a teaching model that is fundamentally based on the use of modified games, whose purpose is for students to learn the tactical aspects of a certain sport, by way of modified versions of the real game.  Later on, we have gone further into depth into a new way of understanding the teaching-learning process in sport, non-Linear Pedagogy, which is based on manipulating the relevant determining factors (task, environment and individual) to increase information sources and thus be able to guide students towards obtaining their objectives.  Within non-linear pedagogy, verbal instruction (e.g., questioning) is considered to be a determining factor that attempts to channel the search for tactical solutions within a learning environment.  Finally, we end the article with a section that refers to practical applications, where we purport to give a series of guidelines on how to implement questioning as a didactical resource whose aim is to improve students' tactical action capacity.